Equilíbrio, funções executivas e quedas de idosos com demência de Alzheimer: um estudo longitudinal - Pedroso, Renata Valle [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Falls among older people is a major clinical problem due to its high incidence, with consequent implications for the health and care costs. Elderly patients with dementia of Alzheimer type (AD) are more susceptible to falls due to the impairment of executive functions and gait, with the risk of falls 3 times higher than non-demented elderly. This study used a longitudinal design and aimed to analyze the effects of a regular and systematized physical activity program on the frequency of falls in patients with AD. Additionally, we aimed to correlate the frequency of falls with the executive functions and equilibrium, after and before the physical activity program. The study included 21 patients with clinical diagnosis of AD, divided into two groups: control group (CG), composed of 11 subjects not engaged in any systematized physical activity and training group (TG): 10 seniors who participated in the Cinesioterapia Functional and Cognitive in Elderly with Alzheimer's disease program (PRO-CDA). The physical activity program lasted four months, with weekly frequency of three times, with each session lasting 60 minutes. Were administered the Mini-Mental State Examination (MMSE) to assess cognitive functioning and global score of the Clinical Dementia Rating (CDR) to classify the severity of dementia. For the evaluation of executive functions were used the Clock Drawing Test (TDR) and Frontal Assessment Battery (FAB). In addition, we used the Functional Balance Scale, Berg test (EEFB) and Timed Up-and-Go (TUG) to assess the equilibrium and risk of falls. Falls were recorded by means of a questionnaire, which included the number of falls in the last four months. Analyzing the results, it was observed that TG obtained significant improvements in equilibrium and in executive functions, highlighting the beneficial effects of physical activity in these variables... (Complete abstract click electronic access below)

As quedas entre pessoas idosas constituem um dos principais problemas clínicos devido à sua alta incidência, às conseqüentes complicações para a saúde e aos altos custos assistenciais. Idosos com demência do tipo Alzheimer (DA) são mais susceptíveis às quedas devido ao comprometimento das funções executivas e alterações na marcha, com risco de quedas 3 vezes maior que idosos não-dementes. Este estudo, de delineamento longitudinal, objetivou analisar os efeitos de um programa de atividade física regular e sistematizada na freqüência de quedas de idosos com DA. E ainda, teve como objetivo correlacionar frequência de quedas com as funções executivas e com o equilíbrio pré e pós-programa de atividade física. Participaram do estudo 21 idosos com diagnóstico clínico de DA, distribuídos em dois grupos: Grupo Controle (GC), composto por 11 idosos não praticantes de atividade física sistematizada; Grupo Treinamento (GT): 10 idosos que participaram do Programa de Cinesioterapia Funcional e Cognitiva em Idosos com Doença de Alzheimer (PRO-CDA). O programa de atividade física teve duração de quatro meses, com freqüência semanal de três vezes, sendo cada sessão com duração de 60 minutos. Foram aplicados o Mini-Exame de Estado Mental (MEEM) para se avaliar o funcionamento cognitivo global e o Escore de Avaliação Clínica da Demência (CDR) para se classificar a gravidade da demência. Para a avaliação das funções executivas foram utilizados o Teste do Desenho do Relógio (TDR) e Bateria de Avaliação Frontal (BAF). Além disso, foram utilizados a Escala de Equilíbrio Funcional de Berg (EEFB) e o teste Timed Up-and-Go (TUG) para se avaliar o equilíbrio e risco de quedas. As quedas foram verificadas por meio de um questionário, no qual constava o número de quedas ocorridas nos últimos quatro meses. Analisando os resultados, observou-se... (resumo completo, clicar acesso eletrônico abaixo)
Keywords: Equilibrio; Educação fisica; Idosos; Educação física adaptada; Atividade física; Patients; Physical activity